Dose-dependent protective effect of sildenafil citrate on testicular injury after torsion/detorsion in rats - Yildiz, H.; Durmus, A. S.; Simsek, H.; Yaman, M. (Wiley, 2012)
This experiment was designed to investigate the effect of sildenafil citrate on testicular injury after unilateral testicular torsion/detorsion (T/D). Thirty-seven adult male Wistar albino rats were divided into four groups: sham operated group (group 1), T/D+ saline (group 2), T/D+ 0.7 mg sildenafil citrate (group 3) and T/D+ 1.4 mg sildenafil citrate (group 4). Testicular torsion was created by rotating the right testis 720 degrees in a clockwise direction for 2 h in other groups, except for group 1, which was served as sham group. The level of GSH (P < 0.05) in the testis in the group 2 were significantly lower (P < 0.05) and the levels of MDA and NO (P < 0.01 for both) in the testis were significantly higher when compared with those of the group 1. Administration of low dose sildenafil citrate prevented the increases in MDA and NO levels and decreases in GSH values induced by testicular torsion. However, administration of high dose sildenafil citrate did not have any effect on these testicular tissue parameters (P > 0.05). Also, mean values of seminiferous tubules diameters, germinal cell layer thicknesses and mean testicular biopsy score were significantly better in group 3 than groups 2 and 4. These results suggest that T/D injury occurred in testis after unilateral testicular T/D and that administration of low dose sildenafil citrate before detorsion prevents ischemia/reperfusion cellular damage in testicular torsion. Sildenafil citrate probably acts through reduction of reactive oxygen species and support antioxidant enzyme systems.
Keywords: Ischemia-reperfusion damage; rat; sildenafil citrate; testicular torsion